Small for Gestational Age Newborns in French Guiana: The Importance of Health Insurance for Prevention - Lindsay Osei; Lindsay Osei; Lindsay Osei; Nicolas Vignier; Nicolas Vignier; Nicolas Vignier; Mathieu Nacher; Juliette Laumonnier; Claude Conan; Loreinzia Clarke; Akoï Koivogui; Sabrina Covis; et al. (Frontiers Media S.A., 2024)
Objectives: Small for gestational age (SGA) newborns have a higher risk of poor outcomes. French Guiana (FG) is a territory in South America with poor living conditions. The objectives of this study were to describe risk factors associated with SGA newborns in FG.Methods: We used the birth cohort that compiles data from all pregnancies that ended in FG from 2013 to 2021. We analysed data of newborns born after 22 weeks of gestation and/or weighing more than 500 g and their mothers.Results: 67,962 newborns were included. SGA newborns represented 11.7% of all newborns. Lack of health insurance was associated with SGA newborns (p < 0.001) whereas no difference was found between different types of health insurance and the proportion of SGA newborns (p = 0.86). Mothers aged less than 20 years (aOR = 1.65 [1.55-1.77]), from Haiti (aOR = 1.24 [1.11-1.39]) or Guyana (aOR = 1.30 [1.01-1.68]) and lack of health insurance (aOR = 1.24 [1.10-1.40]) were associated with SGA newborns.Conclusion: Immigration and precariousness appear to be determinants of SGA newborns in FG. Other studies are needed to refine these results.